Ribosome Recycling Factor and Release Factor 3 Action Promotes TnaC-Peptidyl-tRNA Dropoff and Relieves Ribosome Stalling during Tryptophan Induction of tna Operon Expression in Escherichia coli - Gong, Ming (American Society for Microbiology, 2007)
Upon tryptophan induction of tna operon expression in Escherichia coli, the leader peptidyl-tRNA, TnaC- [Formula: see text] , resists cleavage, resulting in ribosome stalling at the tnaC stop codon. This stalled ribosome blocks Rho factor binding and action, preventing transcription termination in the tna operon's leader region. Plasmid-mediated overexpression of tnaC was previously shown to inhibit cell growth by reducing uncharged [Formula: see text]  availability. Which factors relieve ribosome stalling, facilitate TnaC- [Formula: see text]  cleavage, and relieve growth inhibition were addressed in the current study. In strains containing the chromosomal tna operon and lacking a tnaC plasmid, the overproduction of ribosome recycling factor (RRF) and release factor 3 (RF3) reduced tna operon expression. Their overproduction in vivo also increased the rate of cleavage of TnaC- [Formula: see text] , relieving the growth inhibition associated with plasmid-mediated tnaC overexpression. The overproduction of elongation factor G or initiation factor 3 did not have comparable effects, and tmRNA was incapable of attacking TnaC- [Formula: see text]  in stalled ribosome complexes. The stability of TnaC- [Formula: see text]  was increased appreciably in strains deficient in RRF and RF3 or deficient in peptidyl-tRNA hydrolase. These findings reveal the existence of a natural mechanism whereby an amino acid, tryptophan, binds to ribosomes that have just completed the synthesis of TnaC- [Formula: see text]. Bound tryptophan inhibits RF2-mediated cleavage of TnaC- [Formula: see text] , resulting in the stalling of the ribosome translating tnaC mRNA. This stalling results in increased transcription of the structural genes of the tna operon. RRF and RF3 then bind to this stalled ribosome complex and slowly release TnaC- [Formula: see text]. This release allows ribosome recycling and permits the cleavage of TnaC- [Formula: see text]  by peptidyl-tRNA hydrolase.